Pollen collection and honey bee forager distribution in cantaloupe - Reyes-Carrillo, José Luis; A. Eischen, Frank; Cano-Ríos, Pedro; Rodríguez Martínez, Rafael; Nava Camberos, Urbano (Instituto de Ecología, A.C., 2007)
Honey bee (Apis mellifera, L.) pollen collection and forager distribution were examined during the 2002 summer in a cantaloupe (Cucumis melo, L., Cruiser cv ) field with plastic mulch and drip irrigated. The experimental site was located near the INIFAP Campo Experimental La Laguna, Matamoros, Coahuila within La Laguna region, Mexico. Two trials were conducted in the same location, but were separated by a 800 m wide pecan orchard. Both cantaloupe trials were planted the same date. Trial 1. Nine honey-bee hives were placed in a three hectare field at the start of bloom. Each hive was fitted with a modified-Ontario pollen trap. The pollen was collected one day a week from each colony every hour beginning from 8:30 hr to 14:30 hr during the first four blooming weeks of the crop. Trial 2. Three weeks after the start of bloom, in a ten-ha field 30 honey bee colonies were located. In four randomlyselected rows of 105 m long, 10 m transects at 25, 50, 75 and 100 m distances from the apiary were marked. The foraging bees were counted simultaneously at the transects every half hour from 7:30 hr until 20:30 hr at the same pollen collection-day during the third week of cantaloupe bloom. Pollen collection was higher early in the morning (22.6 g per colony), dropping to medium amount from 9:30 hr (13.7 g), 10:30 hr (12.5 g) to 11:30 hr (9.5 g) and remaining low from 12:30 through the afternoon (less than 2.6 g per colony; p< 0.05). The distribution pattern showed that bees were in the cantaloupe after 8:00 hr, reaching a maximum between 10:30 hr and 14:30 hr when the bees began to decrease, until foraging flights ceased completely at about 20:30 hr. No statistical differences were found in the number of foraging bees among the evaluated distances from the apiary.